Enhanced adsorption and photocatalytic degradation of organics using La-doped g-C3N4 with Ag NPs - Kingsley Igenepo John; Touma B. Issa; Goen Ho; Aleksandar N. Nikoloski; Dan Li (Water Cycle)
In the present study, a series of La-doped g-C3N4 with Ag nanoparticles (NPs) decoration was synthesized via one-pot thermal pyrolysis and wet impregnation. As compared with the bulk g-C3N4 (BCN), La-modified g-C3N4 or Ag-modified g-C3N4, the optimal La-doped g-C3N4 with Ag NPs decoration (Ag-0.8/LaCN-1) showed improved methyl orange (MO) adsorptive capacity and higher photocatalytic activity, because of the synergistic effect of La doping and Ag NPs decoration. Adsorption kinetic and isotherm models were employed to study the adsorption mechanism. The best fit of the experimental data was obtained using the pseudo-second-order (PSO) kinetic model and the Redlich-Peterson isotherm model. It indicated that the MO adsorption using Ag-0.8/LaCN-1 was mainly governed by chemisorption; the process appeared to follow neither an ideal monolayer nor a multilayer but a hybrid mechanism. The MO adsorptive (30 min) removal and photocatalytic degradation (80 min) rate using Ag-0.8/LaCN-1 was seen at around 49.6 and 13.1 times that of BCN, respectively. At pH = 6, the good MO adsorption could be mainly the result of π – π interaction and complexation; whilst the good photocatalytic efficiency was ascribed to improved visible light absorption, charge carrier separation and transfer. Superoxide radicals and holes were proven as the main reactive species for the high MO photocatalytic degradation, by conducting the scavenger test and ESR analysis. The as-prepared Ag-0.8/LaCN-1 displayed good reusability with approximately a 3% loss in the total MO removal% after five consecutive runs of tests. Good stability was observed, recording only ca. 0.25% and 0.01% leaching of Ag and La dopants from Ag-0.8/LaCN-1, respectively, suggesting its robustness for practical use.